Dimensions of the Eighth French Campaign on Tunisia and its Results 669 AH / 1270 AD (Latakia University Journal - Arts and Humanities Sciences Series, 2019)
The French campaigns led by the Western European to the Arab world, according to the prevailing belief is to rid Jerusalem of Muslims, but the underlying and hidden behind it is to achieve a range of political and economic interests serve Europe and make it in the forefront, However, it did not prevent Louis IX from carrying out his campaign. He held many alliances and agreements in which he wanted to achieve his projects and objectives in Africa. The campaign of Louis IX on Egypt and then on Tunisia was a means, not an end. , Means of access To the Holy Land and to control it, this is the belief of Louis IX, who went ahead in processing the requirements of the campaign of several equipment and headed its own leadership, when he got the full support of the religious authority and political support by the kings of Europe and especially from his brother Charles Anju, as a result of those alliances that thought That it would achieve what it wanted, given the political situation of the unrest and revolutions that had erupted in Tunisia from time to time, has created the conditions appropriate for the march to Tunisia and control, but the quest that Lewis wanted to expand and control of Tunisia failed and did not achieve its objectives due to circumstances The Beard that hit him, and shortly after the story ended adventurer who wanted to underscore the story of his life and honors his memory to achieve its objectives on the expansion of religious and secular levels.